Upaya Percepatan Penurunan Stunting Melalui Peningkatan Kesadaran Dan Pengetahuan Masyarakat Terhadap Faktor Risiko Di Desa Jenar, Kabupaten Sragen - Karima, Muzakiya Lailatul (Faculty of Medicine, Universitas Sebelas Maret, 2023)
Introduction: Stunting is a problem that is currently a concern for the Indonesian government because the incidence rate is quite high. In 2021, the stunting incidence rate was obtained at 24.4%. The government is trying to reduce the incidence of stunting to 14% by 2024. In this regard, this community service activity aims to make the stunting reduction acceleration program a success.Methods: This community service activity was carried out in Jenar Village, Jenar District, Sragen Regency, which is one of the stunting focus locations from July 15 to August 12, 2022 with large group counseling methods and interventions to the community in the form of anthropometric measurements and healthy gymnastics.Results and discussions: The participation and attention of mothers in activities is very good, partner groups actively contribute to the procurement of activity needs and actively share experiences about child growth and development and a healthy lifestyle. The impact of counseling activities can increase the knowledge and awareness of the people of Jenar Village regarding the risk factors for stunting and a healthy lifestyle.Conclusion: Community service activities in the context of efforts to accelerate the reduction of stunting in Jenar Village are very useful and are expected to play a role in reducing the incidence of stunting.